2019
DOI: 10.1016/j.carbpol.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy nano-emulsification approach as a simple strategy to prepare positively charged ethylcellulose nanoparticles

Abstract: 16Positively charged ethylcelulose nanoparticles have been obtained from 17 alkylamidoammonium/Span 80 based nano-emulsion templates. Oil-in-water 18 polymeric nano-emulsions form in a broad range of oil-to-surfactant ratios and water 19 contents above 75 wt% by a low-energy method at 25ºC. Nano-emulsions with a 20 water content of 90 wt% showed droplet sizes typically below 300 nm and high 21 positive zeta potential values (~55 mV). If oleylamine is added to the system, smaller 22 droplet sizes and higher zet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
2
11
2
Order By: Relevance
“…As shown in Figure 2b, the nano-emulsions formed display typically a translucent to transparent appearance, depending on the O/S ratio and the HEPES 20 mM content, with a bluish shine due to the Tyndall effect. This appearance is strikingly different from previously reported systems prepared with the same cationic surfactant (CatA) but different nonionic surfactants (namely Span 80 and Cremophor WO7) which showed higher opacity (Leitner et al 2019;Calderó et al 2019). It is also worth mentioning that in the system described herein, the nano-emulsion domain is considerably larger than in the latter mentioned systems.…”
Section: Transfection Efficiency Assaycontrasting
confidence: 97%
See 3 more Smart Citations
“…As shown in Figure 2b, the nano-emulsions formed display typically a translucent to transparent appearance, depending on the O/S ratio and the HEPES 20 mM content, with a bluish shine due to the Tyndall effect. This appearance is strikingly different from previously reported systems prepared with the same cationic surfactant (CatA) but different nonionic surfactants (namely Span 80 and Cremophor WO7) which showed higher opacity (Leitner et al 2019;Calderó et al 2019). It is also worth mentioning that in the system described herein, the nano-emulsion domain is considerably larger than in the latter mentioned systems.…”
Section: Transfection Efficiency Assaycontrasting
confidence: 97%
“…It is worth mentioning that HEPES solution contains zwitterionic molecules. The conductivity values attained, as well as the conductivity variation as a function of the aqueous component content are comparable to those obtained with similar systems described earlier, containing the same cationic surfactant but different nonionic surfactants, namely Span 80 (Leitner et al 2019) and Cremophor WO7 (Calderó et al 2019). Phase inversion takes place at about 25 wt% HEPES solution.…”
Section: Supplementary Information Supplementary Informationsupporting
confidence: 86%
See 2 more Smart Citations
“…Ethylcellulose nanoparticles show a negative surface charge when prepared with non-ionic ethoxylated surfactants by this approach [8,13]. However, it has been recently demonstrated that they can be endowed with a positive surface charge by using a surfactant mixture including a cationic amphiphilic molecule [12,14]. Positive surface charge of nanoparticles can be exploited to enhance cell uptake [15]; to promote adsorption to negatively charged surfaces [16]; to bind electrostatically molecules such as nucleic acids, drugs, inorganic nanoparticles, biomolecules [17], etc.…”
Section: Introductionmentioning
confidence: 99%